Allometric Growth of the Freshwater Crab Potamon algeriense (Bott, 1967) (Decapoda, Brachyura, Potamidae) in Oued Zegzel, a Mountain Stream, in the Northeast of Morocco - Fadlaoui, Soufiane; Mahjoub, Mohammed; El Asri, Ouahid; Melhaoui, Mohammed (International Journal of Zoology, 2019)
A morphometric study has been carried out for the first time on the population of the freshwater crab Potamon algeriense inhabiting Oued Zegzel, a tributary of the Lower Moulouya River, in the northeast of Morocco. Crabs were collected monthly over one year (October 2017 to September 2018) by excavating burrows and searching under blocks. A total of 669 crabs were obtained, 291 females and 378 males. Regression analysis was performed among carapace width (CW), as the reference dimension, and wet weight (WW), carapace length (CL), length and width of abdomen (AL and AW), and length and width of the cheliped (ChL and ChW) were chosen as dependent variables, using the allometric method. Based on Somerton’s technique, the onset of sexual maturity was estimated to occur at around 27mm CW for males and 32mm CW for females. The growth patterns recorded for P. algeriense are associated with the species reproductive strategy, i.e., preparation of body parts involved in female acquisition and egg incubation, like the male cheliped and the female abdomen, respectively. Among the 291 females sampled, 10.20% were left-handed and 89.80% were right-handed, while among the 378 males examined, 10.32% were left-handed and 89.68% were right-handed. It was concluded that the cheliped width and the abdominal width of P. algeriense are the morphometric variables most appropriate to estimate the size at the beginning of the sexual maturity for males and females of this species, respectively.